PENGEMBANGAN MULTIMEDIA INTERAKTIF SEBAGAI ALAT BANTU PEMBELAJARAN DENGAN MODEL PBL UNTUK PENINGKATAN HASIL BELAJAR MATEMATIKA - Novia Margarita (Universitas Pendidikan Ganesha, 2018)
This study aims to develop interactive multimedia as a tool for improving the results of learning mathematics of grade 4 elementary school (SD). Research method with Research and Development (RnD) with ASSURE development model with 6 stages: 1) analyze learners characteristic, 2) state objectives, 3) select modify or design method, media or materials, 4) utilize media and materials, 5) learners participation, 6) evaluate and revise. The validity and interactive multimedia materials and products are tested by expert tests using the validation sheet instrument. Validate material experts with an 86% percent score with criteria indicating very high category. Media validation with 88% percentage score with very good category. The practicality of interactive multimedia products was tested with limited trials, 2 SDs did not use media and 2 SDs using media with PBL models during the learning process. The results of the limited trial results shown on 2 SDs that did not use media resulted in average pretest values of 72.56 and posttest 80.12 and sig. (2-tailed) 0.004. Furthermore, in the 2 SDs using media, the average pretest 75.74 and posttest 83.62 and sig. (2-tailed) 0.000 were generated. Based on the interactive multimedia developed and valid material contained in interactive multimedia can bring learners to learn indirectly and can learn independently. Keywords: Research and Development (RnD), Interactive Multimedia, PBL Model, Mathematics